63.0k views
12 votes
X+y=-1 x-y=-7 by elimination

User Raevilman
by
6.1k points

2 Answers

5 votes

jhhhelp

hsjagwnahsususj

User Doraemon
by
6.1k points
4 votes

Answer:

(x, y) = (-4, 3)

Explanation:

x + y = -1 $|Rightarrow$ x = -1 - y

x - y = -7

Substituting the value of x (first equation) into the second equation, we get:

(-1 - y) - y = -7.

Simplifing, we get:

-1 -2y = -7

-2y = -6

y = 3.

Now that we know the value of y, we can solve the value of x by substituting y into the first equation. We get:

x = -1 - 3

x = -4

User YFeizi
by
6.0k points